2015
DOI: 10.1210/jc.2014-2675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lifestyle Intervention in Pregnancy and Anthropometrics at Birth on Offspring Metabolic Profile at 2.8 Years: Results From the Lifestyle in Pregnancy and Offspring (LiPO) Study

Abstract: Early childhood metabolic risk factors were unaffected by lifestyle interventions in obese pregnant women. Offspring of obese mothers who participated in the LiP study were comparable to offspring of normal-weight mothers, possibly indicating a general beneficial effect of trial participation. BAC and BW were both associated with later metabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
69
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 30 publications
7
69
2
1
Order By: Relevance
“…These results from studies designed as a gestational lifestyle counselling program are in line with our results. On the other hand the results from the Danish study [24] intended to give a postnatal lifestyle counselling differ from our findings. The women in the intervention group in the present study were offered, in addition to the gestational intervention program, an individual visit every six months during the first two years after childbirth in order to discuss behaviour regarding nutrition and physical activity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results from studies designed as a gestational lifestyle counselling program are in line with our results. On the other hand the results from the Danish study [24] intended to give a postnatal lifestyle counselling differ from our findings. The women in the intervention group in the present study were offered, in addition to the gestational intervention program, an individual visit every six months during the first two years after childbirth in order to discuss behaviour regarding nutrition and physical activity.…”
Section: Discussioncontrasting
confidence: 99%
“…The increase of the ZBMI and ZWL/H, between 2 and 4 years of age was slower among the offspring in the postpartum intervention group than in the control group [14]. In a recent Danish follow-up study of a gestational intervention program for obese women, no ZBMI differences at three years of age were detected between the intervention-and control groups [24]. These results from studies designed as a gestational lifestyle counselling program are in line with our results.…”
Section: Discussionsupporting
confidence: 91%
“…32 Observational studies that follow children born of mothers who were participants in lifestyle interventions targeting gestational weight gain or gestational diabetes have not found a ''spillover'' effect on childhood obesity or metabolic profile. [32][33][34] Grounding interventions in life course theoretical models and developing solution-focused intervention strategies that cover both prenatal and early postnatal behavioral changes may be needed to advance the evidence base in this area. 1 In short, comprehensive and effective childhood obesity prevention will require targeting factors at different developmental windows in order to meaningful affect the prevalence of obesity in the population.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our study, the few studies that have reported on infant growth after prenatal interventions have found no changes in infant growth. This includes two previous European studies with null results 27,28 and one study in the United States evaluating a walking intervention during pregnancy that followed babies to 6 months postpartum. 29 Biological explanations for these null findings have been proposed.…”
Section: Discussionmentioning
confidence: 99%